2021
DOI: 10.1016/j.scitotenv.2021.146092
|View full text |Cite
|
Sign up to set email alerts
|

Escaping to nature during a pandemic: A natural experiment in Asian cities during the COVID-19 pandemic with big social media data

Abstract: Mass social media data enabled an extensive investigation into greenspace use patterns. • Urban greenspace use increased in four Asian cities during the COVID-19 outbreak. • During the COVID-19 outbreak, residents preferred large nature parks close to city centers.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
86
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 50 publications
11
86
2
1
Order By: Relevance
“…Second, air pollution may exacerbate the SARS-CoV-2 infection risk [ 69 ], yet green space can reduce exposure to air pollution, thereby decreasing the virus infection risk [ 67 ]. Other studies also found that green space usage increased during the pandemic [ 70 ], and the availability of green space decreases racial disparity in virus infection rates [ 71 ]. However, two studies suggested a positive association between green space and virus infection risk [ 48 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, air pollution may exacerbate the SARS-CoV-2 infection risk [ 69 ], yet green space can reduce exposure to air pollution, thereby decreasing the virus infection risk [ 67 ]. Other studies also found that green space usage increased during the pandemic [ 70 ], and the availability of green space decreases racial disparity in virus infection rates [ 71 ]. However, two studies suggested a positive association between green space and virus infection risk [ 48 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mental health benefits of access to nature during the pandemic have been demonstrated, but this does not always reflect purposive engagement. While increased visitation to urban greenspaces during the pandemic has been reported across a number of studies internationally [ 34 , 38 , 72 , 73 ], some studies have reported decreases in the time people spent in urban greenspaces during the COVID-19 pandemic [ 32 , 40 ] due to mobility restrictions and fear of infection. Individuals who had greater nature engagement during the pandemic typically had better mental health [ 17 , 20 , 35 , 38 , 41 ] and often reported that nature was important for supporting their mental health [ 31 , 40 , 73 ], helping them cope with lockdowns [ 36 , 38 ], and gave them feelings of “being away” [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, having access to public urban greenspaces [ 32 , 33 , 34 ] and private outdoor spaces [ 35 , 36 ], living in greener neighbourhoods [ 20 , 37 , 38 ], and having ‘natural’ views from home [ 36 , 37 , 39 ] have been linked with better mental health across a range of populations during the pandemic. Beyond access and incidental exposure to nature, purposive time spent in nature during the COVID-19 pandemic has also been linked with better mental health [ 17 , 20 , 26 , 31 , 34 , 35 , 38 , 39 , 40 , 41 ]. Only two of these studies exploring the influence of nature focused on young people specifically, and were limited to student samples in the USA [ 17 ] and Bulgaria [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some areas, increased greenspace utilization was used strategically in direct response to increased disease prevalence. For example, in several East Asian cities, greenspace utilization increased by 5.3% for every 100 additional new COVID-19 cases reported (Lu et al, 2021b). The cause of increased greenspace utilization is multifactorial.…”
Section: Introductionmentioning
confidence: 99%